GADGET UTILITY USED BY ELEMENTARY SCHOOL STUDENTS FOR ONLINE LEARNING - Ferdinanda Itu Meo; Tuti Tuti; Ilinawati Ilinawati (Journal of English Educational Study (JEES), 2021)
This study aims at analyzing the usage of gadget for elementary school in online learning.  This research is descriptive qualitative,  where the researchers took 20 students consisted of 10 females and 10 males from various Elementery school in sintang district as  participants. In collecting the data, the reseachers used interview and questionaires. The questionaires consisted of 8 questions with scale likerts method. In conducting the interview, the researcher prepared 5 questions in the form of open ended questionnaires. This interview aims to confirm the data from the questionnaires  There are 3 things that are focused by researchers, namely gadget ownership, gadget use, and parental monitoring of gadget use.The result of interview and questionaires showed that gadgets are specifically designated to support learning activities during the pandemic. In addition, parents strongly support their children to use gadgets in the context of online learning by giving their children their own gadgets to study, but they are still under parental supervision and time restrictions on gadget use.